The Problem-Based Learning: How the effect on student critical thinking ability and learning motivation in COVID-19 pandemic? - Rifqi Festiawan; Lim Boon Hooi; Prisca Widiawati; I Ketut Yoda; Adi S; Muhammad Sigit Antoni; Arifin Ika Nugroho (Journal Sport Area, 2021)
In the period of the Covid-19 pandemic, lecturers were confronted with difficulties to give a more intelligent learning model, one of which was a problem-based learning model. The reason for this investigation was to decide the impact of issue put together learning models with respect to understudies' basic reasoning abilities and acquiring inspiration, particularly in actual training learning. This exploration is a genuine test with a randomized pretest-posttest control bunch plan. The population is all understudies of class X, XI, and XII. The testing method utilizes straightforward irregular inspecting. The examples utilized in this examination were 112 individuals. The examination instrument utilized was target tests as various decision inquiries for basic reasoning abilities and mastering inspiration polls. The information investigation utilized was Paired example t-test and Independent example t-test. The consequences of his exploration are there is an impact of issue put together learning models with respect to understudies' basic reasoning abilities. There is an impact of the issue put together learning model with respect to understudy inspiration. The problem-based learning model is more compelling than the immediate showing model for understudies' basic deduction abilities in actual schooling mastering. The model of problem-based learning has a more beneficial outcome than the immediate encouraging model on understudies' learning inspiration in actual schooling learning. From these outcomes, it very well may be presumed that there is an impact of issue put together learning with respect to basic reasoning abilities and understudy inspiration, and issue based learning shows better outcomes contrasted with direct educating.